Comparative study on characteristics and mechanism of levofloxacin adsorption on swine manure biochar. (May 2022) - Wang, Zhirou; Jang, Hyun Min
Highlights: Swine manure-derived biochar was prepared under different temperatures (300–900 ℃). Swine manure-derived biochar was applied to remove levofloxacin in solution. Adsorption kinetics and isotherm mechanisms were investigated. Temperature is highly related to the characteristics of biochar. Adsorption capacity (158 mg/g) is comparable with that of activated carbons. Abstract: This study evaluated the relationship between pyrolysis temperature (300–900 ℃), characteristics of swine manure (SM)-derived biochar (BC), and its adsorption of levofloxacin (LEV). The surface structure and chemistry of SM-derived BCs were characterized using Brunauer-Emmett-Teller analysis, scanning electron microscopy, Fourier-transform infrared spectroscopy, X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. According to the characteristic analysis, the surface area and graphitization degree of SM-derived BC increased as temperature rose. The highest adsorption capacity was achieved by BC-900 (158 mg/g); this level was higher than that achieved in previous studies and comparable to that of commercial activated carbons. Characterization and adsorption experiments indicated that pore-filling, π–π stacking interaction, π–π electron donor–acceptor, H-bonding, and hydrophobic interactions each played a critical role in the adsorption of LEV on SM-derived BC. Collectively, this study confirms the potential utility of SM-derived BC for the removal of antibiotics.